2013
DOI: 10.1115/1.4007480
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamics of Wake Blade Interaction in Axial Flow Turbines: Combined Experimental and Computational Study

Abstract: This paper reports on insights into the detailed thermodynamics of axial turbine nozzle guide vane (NGV) wakes as they interact with the rotor blades. The evidence presented is both computational and experimental. Unsteady Reynolds-averaged Navier–Stokes (RANS) simulations are used to compare the experimental observations with theoretical predictions. Output processing with both Eulerian and Lagrangian approaches is used to track the property variation of the fluid particles. The wake is found to be hot and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Generally, the flow parameters in both cases evolved very closely. Their baselines are similar and in good agreement with flow-parameter evolution evidenced in past studies and experiments reported on by Marchal and Sieverding, 47 Strickland et al, 44 Langston, 48 Sonoda, 50 Goldstein and Spores, 45 Sieverding et al, 46 Sieverding, 49 and Rose et al 22,23 The flow vortex in both cases began at stator blade's LE and developed along the blade profile. The vortex was strong in the rotor where rotation impacts occur, as explained in detail in section ''Baseline 1D; 2D full HPT flow-path calculation.''…”
Section: Formation and Distribution Of No X And So X Throughout The Ssupporting
confidence: 87%
See 2 more Smart Citations
“…Generally, the flow parameters in both cases evolved very closely. Their baselines are similar and in good agreement with flow-parameter evolution evidenced in past studies and experiments reported on by Marchal and Sieverding, 47 Strickland et al, 44 Langston, 48 Sonoda, 50 Goldstein and Spores, 45 Sieverding et al, 46 Sieverding, 49 and Rose et al 22,23 The flow vortex in both cases began at stator blade's LE and developed along the blade profile. The vortex was strong in the rotor where rotation impacts occur, as explained in detail in section ''Baseline 1D; 2D full HPT flow-path calculation.''…”
Section: Formation and Distribution Of No X And So X Throughout The Ssupporting
confidence: 87%
“…The potential field of the moving rotor causes finites (∂T=∂x, ∂p=∂x, and ∂U=∂x), which, according to equations (1)-(3) cause the total temperature, pressure, and velocity to vary. 22,23,43 The flow variation results in Figure 4 are in good agreement with the experimental results of Strickland et al, 44 Goldstein and Spores, 45 Sieverding et al, 46 and Rose et al 22,23 To better understand the mechanism forming the vortex from blade LEs to blade TEs, Goldstein and Spores 45 combined various visualizations and measurements described in the literature (see, among others, Marchal and Sieverding, 47 Langston, 48 Sieverding, 49 and Sonoda 50 ). This mechanism is illustrated in Figure 5, which shows the major vortices, labeled 1-7, and primary regions of interest, labeled A-K, in the turbine passage.…”
Section: Baseline 1d; 2d Full Hpt Flow-path Calculationsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the unsteady stator-rotor interaction is an important contributor to the overall turbine performance, it is a complex mechanism and it cannot be said whether the weaker interaction is always more beneficial or whether the stronger interaction should be the aim, as proposed by Rose et al 23 The positivity or negativity of the stator-rotor interaction can also vary from hub to shroud, as shown by Yamada et al 24 and Gaetani et al 2,18 In addition, Gaetani et al 25 reported that the wake-induced interaction decreased the efficiency with larger clearances and the vortex-induced interaction with small clearances.…”
Section: An Example Of the Mixing Loss Evolution Is Plotted Inmentioning
confidence: 99%
“…Thirdly, the unsteady computations simulate spatiotemporal loss production associated with wake transport and stretching (Ref. 15) to some degree of accuracy (grid dependent). Lastly, Haselbach et al (Ref.…”
Section: Background and Motivationmentioning
confidence: 99%